INTEGRATING A BILINGUAL TO IMPROVE LEARNING OUTCOMES AT AT SRJ STATE ELEMENTARY SCHOOL - Afifah, Lia nur; Pradana, Dian Arief; Anwar, Saiful; Rohmah, St. Shabibatul (English Language Teaching Methodology, 2024)
In today’s globalized world, English language proficiency is essential for academic and professional success. This study investigated the effectiveness of a bilingual learning approach in improving English language skills among second grade students at Sumberrejo Elementary School in Banyuwangi. The study involved 16 students and implemented a strategy that integrated Indonesian as a first language (L1) with English as a second language (L2). Using Classroom Action Research (CAR) methodology, this study conducted tests that showed an increase in students’ English language skills, with an average score increasing from 79.6% to 86.1%.These findings highlight the benefits of a bilingual approach. Integrating L1 and L2 in the learning process facilitates better understanding and retention of English concepts, reduces cognitive load, and increases students’ self-confidence. The use of culturally relevant local materials engages students by making learning more relevant and stimulating.This study underscores the importance of using students’ mother tongue as a scaffold in English language learning. The bilingual method successfully overcomes language barriers and creates an inclusive classroom atmosphere, improving linguistic skills and enhancing cognitive abilities such as problem solving.Despite the diverse backgrounds of students, the bilingual approach effectively meets individual learning needs and preferences. This study concludes that the implementation of bilingual strategies, complemented by relevant local content, can significantly improve English teaching and learning in primary schools.